Thyristor‐based modular multilevel converter‐HVDC systems with current interruption capability. Issue 12 (5th September 2019) - Wang, Qingsong; Deng, Fujin; Liu, Chengkai; Heng, Qian; Chen, Zhe
Abstract : The modular multilevel converter (MMC) is an attractive option for high‐voltage direct‐current (HVDC) transmission applications. The dc line short‐circuit fault is one of the key challenges for the HVDC system. In this study, a thyristor‐based MMC with current interruption capability is proposed, where the IGBT with anti‐parallel thyristor is employed to realise current interruption with the advantages of the simple circuit configuration and less number of power electronic devices. Also, the protection scheme for the thyristor‐based MMC HVDC system under dc lines short‐circuit faults is also proposed, where the fault current can be quickly interrupted by the thyristor‐based MMC. The proposed thyristor‐based MMC HVDC system is not necessary to be disconnected with the ac grid during the dc‐line fault, where the MMC can continue operating and can be used for reactive power regulation before the fault is cleared, and therefore improves the system performance. The simulation and experimental studies are conducted, and the results verify the effectiveness of the proposed thyristor‐based MMC and control scheme.